The potential of digital cash transfers to strengthen the link between humanitarian assistance and social protection - Emma Ford (University of Bath, Centre for Development Studies (CDS), 2017)
Recent years have seen a rise in the use of cash-based assistance but whilst humanitarian contexts lend themselves well to the digitisation of aid, cash assistance remains a very small part of humanitarian aid. This white paper examines how the increased use of digital cash transfer technology which delivers cash to recipients using card-based and mobile phone-based systems, may provide potential opportunities for closer collaboration between humanitarian and development actors working towards achieving collective, sustainable outcomes, as well as enabling a closer link between state provided social protection and humanitarian cash transfers. However, it argues that, in order to preserve the humanitarian imperative 'to do no harm', agencies must take great care to mitigate against the potential negative impacts of the operational challenges of implementing such a policy. The paper first highlights the potential benefits to the actors involved; second, the operational issues; and then discusses in greater depth the ways in which digitisation assists increased synergy between humanitarian assistance and development programmes, also focussing specifically on social protection. [...]
Keywords: 330